Measurement Invariance of a School Readiness Screener for Use in Preschool and Kindergarten. Issue 7 (3rd October 2017) - Edyburn, Kelly L.; Quirk, Matthew; Furlong, Michael
ABSTRACT: Research Findings : Public policy has increasingly focused on expansion of preschool access for underserved students and systematic evaluation of preschool quality and students' readiness for school. However, such evaluation is limited by a lack of thoroughly validated assessments for use with preschool populations. The present study examined the measurement and structural invariance of the Kindergarten Student Entrance Profile (KSEP) across kindergarten and prekindergarten groups to evaluate its potential use across developmental groups. Participants included 522 kindergarten and 548 prekindergarten students in central California. Invariance was tested by fitting a series of multiple-groups confirmatory factor analysis models with parameter constraints across groups. Results indicated that measurement and structural parameters of the KSEP were invariant across kindergarten and prekindergarten groups. Prekindergarten means on both Social–Emotional Readiness and Cognitive Readiness were significantly lower than kindergarten means. Practice or Policy : These results suggest that the KSEP may potentially be used with prekindergarten students to assess school readiness and inform intervention before kindergarten entry.